"Nurses caught in the middle": A qualitative study of nurses' perspectives on the decision to transfer deteriorating nursing home residents to emergency departments in Singapore. Issue 4 (August 2022) - Nguyen, Phuong Thanh; Liaw, Sok Ying; Tan, Apphia Jia Qi; Rusli, Khairul Dzakirin Bin; Tan, Laurence Lean Chin; Goh, Hongli Sam; Chua, Wei Ling
ABSTRACT: Background: Nursing home nurses are pivotal in recognising resident deterioration and initiating the decision-making process on resident transfer to emergency departments. However, their decisions have not been adequately explored in the Asian context which places a strong emphasis on family connection and has a longstanding history of considering end-of-life discussion as a taboo. Aim: To explore the experiences of nursing home nurses surrounding resident transfer to emergency departments during acute deterioration. Methods: A descriptive qualitative study was undertaken. Individual semi-structured interviews were held from October to December 2019 with a purposive sample of 14 nurses from one nursing home in Singapore. Thematic analysis was performed on the data. Findings: Five themes were identified: (i) knowing the residents; (ii) challenges in honouring residents' advance care planning; (iii) family involvement in transfer decisions; (iv) nurses as an intermediary between family and physicians; and (v) struggling to shift from curative to palliative thinking. Discussion: In-depth knowledge of residents facilitated nurses' transfer decisions and physician referrals were made without deliberation. In their decision-making process, nurses negotiated between their own personal value system - a preference for life-sustaining therapies - and balancing the interests and preferences of residents, family members, and physicians. Priority was given to families' decisions even in the presence of established advance care planning. Conclusion: This study highlights the need for further development of family-centred advance care planning in Asian long-term residential care. A greater acceptance of palliative care among nursing home staff and the public may improve the end-of-life care quality for residents.